An overview of collective bargaining and its relation with trade unions in Argentina (2003-2015) - Marticorena, Clara (FCL-UNESP Laboratório Editorial, 2017)
Since the year 2003 in Argentina several studies have focused on the analysis of the political, institutional and economic determinants of collective bargaining, or on the study of its evolution and general characteristics. In spite of the importance of these dimensions, the analysis of the frequency of agreements and its evolution tends to displace, on one hand, theoretical discussions about collective bargaining and, on the other, the study of the contents and of negotiation processes. This paper aims to discuss theoretical elements and empirical results about collective bargaining during this period, and also to reflect on the link between bargaining processes and union organization during post-convertibility.